Conventional and novel imaging modalities in osteoarthritis: current state of the evidence. Issue 3 (May 2015) - Demehri, Shadpour; Hafezi-Nejad, Nima; Carrino, John A.
Abstract : Purpose of review: Imaging modalities are currently an inseparable part of osteoarthritis diagnosis. In this review, we describe the current state of evidence regarding conventional and novel imaging modalities in evaluation of osteoarthritis. Modalities including radiography (qualitative and semi-quantitative assessments), ultrasonography, computed tomography [CT; conventional multidetector CT (MDCT), cone-beam CT (CBCT) and four-dimensional CT (4DCT)], MRI (MRI; semi-quantitative, quantitative and compositional) and PET and their applications are reviewed. Recent findings: Radiography is the modality of choice for initial assessment of osteoarthritis. However, due to its low sensitivity and specificity, numerous recent investigations have proposed MRI as a powerful addition to detect and grade osteoarthritis features, which are not apparent in radiography. Semi-quantitative MRI measurements are feasible to perform in routine clinical practice. Quantitative and compositional MRI measurements have extended the amount of information an MRI examination can provide regarding the three-dimensional shape and tissue composition of articular cartilage. 4DCT and CBCT are introduced as imaging examinations that may reveal biomechanical cartilage abnormalities in osteoarthritis joint by dynamic and weight-bearing evaluations, respectively. Recent PET studies may unveil the underlying metabolic activities that can be associated with osteoarthritis. Summary: In addition to the established role of radiographs, MRI is the advanced modality of choice for detection and quantification of various osteoarthritis features. 4DCT and CBCT may have specified applications when diagnosis of underlying motion abnormality or dynamic changes in weight-bearing situation is suspected. Future studies should elucidate the specific clinical applications of ultrasonography and PET.